Planning sustainable heat networks: governance and sociotechnical practices in Northeast England - William Otchere-Darko; Michael Crilly; Tyne Jenkinson; Caitlin Harper; Emily Ingall-Tombs; Esmee Bryson-Harris; Eleanor Ritchie; Ryan Siu; Sam Wightman; Alexander Kearns (Sustainability Science, 2025)
District heating (DH) forms part of decarbonised energy pathways, potentially offering decentralised, cheap heating for dense urban areas. Entailing both carbonised and decarbonised heat sources, with multiple and overlapping technologies, DH is situated within the milieu of energy and urban planning. This presents questions as to how local governance arrangements and practices are created/emerge to respond to/(co)produce its spatial, energy and technological materialisations. Utilising mixed methods, the study focuses on selected DH projects in Northeast England—a region with historic coal infrastructure and recent heat network projects. Findings first show forms of partnership, outsourcing and subsidiarising as governance arrangements surrounding the DH projects in sharing expertise, resources and risks. These arrangements are implemented through legal agreements, negotiations, reporting mechanisms as well as infrastructure and heat co-production practices. Secondly, these diverse governance arrangements also reflect attempts to address funding, energy security and regulatory issues increasingly refracted through local geothermal endowments and incumbent gas incentives. In effect, the research notes that policy and governance practices should be responsive to a heterogeneous, hybrid and co-produced heatscape, challenging the ideal of transitioning to a uniform DH.